1989
DOI: 10.1111/j.1528-1157.1989.tb05478.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bilirubin Levels with Antiepileptic Drugs

Abstract: The incidence of reduced bilirubin levels in 168 outpatients with epilepsy, compared with levels in 69 controls, has been investigated. Highly significant (p less than 0.001) reductions in average bilirubin levels were noted for carbamazepine (CBZ), phenytoin (PHT), phenobarbital (PB), and multiple drug groups. A marginally significant (p less than 0.05) reduction in bilirubin levels occurred in patients treated with valproate (VPA) which, unlike the other drugs, has not been shown to induce hepatic enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It has been well documented that drugs known to activate constitutive androstane receptor (CAR) (eg, phenytoin and phenobarbital) and/or Pregnane X receptor (PXR) (eg, rifampicin and carbamazepine) upregulate the expression of proteins involved in bilirubin disposition, including UGT1A1 and MRP2, 26,27 and thus reduce serum bilirubin concentrations. 28,29 In fact, phenobarbital and rifampicin have been used in the past to treat hyperbilirubinemia. 29,30 Similarly, efavirenz is known to activate CAR 11,31 and possibly PXR, 32 and it is reasonable to suggest that efavirenz, like these PXR/CAR activators, interacts at ≥1 of these sites to enhance the elimination of bilirubin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that drugs known to activate constitutive androstane receptor (CAR) (eg, phenytoin and phenobarbital) and/or Pregnane X receptor (PXR) (eg, rifampicin and carbamazepine) upregulate the expression of proteins involved in bilirubin disposition, including UGT1A1 and MRP2, 26,27 and thus reduce serum bilirubin concentrations. 28,29 In fact, phenobarbital and rifampicin have been used in the past to treat hyperbilirubinemia. 29,30 Similarly, efavirenz is known to activate CAR 11,31 and possibly PXR, 32 and it is reasonable to suggest that efavirenz, like these PXR/CAR activators, interacts at ≥1 of these sites to enhance the elimination of bilirubin.…”
Section: Discussionmentioning
confidence: 99%
“…A gradual increase in UGT-activity, expressed as bilirubin conjugation, as a function of valproate levels has been demonstrated in vivo in mice. 52 The reduction in total bilirubin levels in patients treated with valproic acid as found by Gough et al, 53 may therefore be explained by higher bilirubin conjugation following an inducing effect of valproic acid on hepatic UGT1A. 52 Additionally, an induced UGT1A1-status may explain why in this particular patient bilirubin levels remained normal, whereas liver-enzymes (that is, gGT and transaminases) increased dramatically after administration of irinotecan.…”
Section: Discussionmentioning
confidence: 87%
“…The finding that UDP-GT levels were lower in the group with hepatic necrosis (compared to those with normal histology) could support the first hypothesis. Clinical studies have demonstrated consistent results in that serum bilirubin levels were significantly reduced in patients receiving phenobarbital, carbamazepine and phenytoin [38]. The mechanism for the reduction of bilirubin level by these drugs has been suggested to be an induction of hepatic microsomal enzyme, glucuronyl transferase [39] or the increased excretion of bilirubin from hepatic cells into bile [40].…”
Section: Discussionmentioning
confidence: 93%
“…The mechanism for the reduction of bilirubin level by these drugs has been suggested to be an induction of hepatic microsomal enzyme, glucuronyl transferase [39] or the increased excretion of bilirubin from hepatic cells into bile [40]. The marginally significant reduction in bilirubin levels in patients treated with VPA which was found by Gough et al [38] has been speculated to be the result of increased excretion of bilirubin from the hepatic cell into the bile. According of patients with VPA-associated hepatotoxicity [21,22,26,27].…”
Section: Discussionmentioning
confidence: 96%